2016
DOI: 10.1073/pnas.1612626113
|View full text |Cite
|
Sign up to set email alerts
|

HIF-KDM3A-MMP12 regulatory circuit ensures trophoblast plasticity and placental adaptations to hypoxia

Abstract: The hemochorial placenta develops from the coordinated multilineage differentiation of trophoblast stem (TS) cells. An invasive trophoblast cell lineage remodels uterine spiral arteries, facilitating nutrient flow, failure of which is associated with pathological conditions such as preeclampsia, intrauterine growth restriction, and preterm birth. Hypoxia plays an instructive role in influencing trophoblast cell differentiation and regulating placental organization. Key downstream hypoxia-activated events were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 67 publications
4
93
1
Order By: Relevance
“…in line with the increasingly recognized role of KDM3A in environmental adaptation and mechanosensation (Chakraborty et al, 2016;Kaukonen et al, 2016;Pedanou et al, 2016). Immunopurification of endogenous KDM3A, two-hybrid screening, and far-Western blotting revealed that KDM3A interacts with actin in vivo and in vitro.…”
Section: Datasets] and S3supporting
confidence: 62%
“…in line with the increasingly recognized role of KDM3A in environmental adaptation and mechanosensation (Chakraborty et al, 2016;Kaukonen et al, 2016;Pedanou et al, 2016). Immunopurification of endogenous KDM3A, two-hybrid screening, and far-Western blotting revealed that KDM3A interacts with actin in vivo and in vitro.…”
Section: Datasets] and S3supporting
confidence: 62%
“…The HIF signaling is a classic oxygen-sensitive pathway to regulate angiogenesis under hypoxic environments. Hypoxia activates Hifdependent expression of lysine demethylase 3A (Kdm3a) which demethylates H3K9 to accelerate Mmp12 expression to facilitate trophoblast invasion and uterine vascular remodeling [38].…”
Section: Histone Methylation In Vascular Development and Maturitymentioning
confidence: 99%
“…Exposure of TS cells to low oxygen can disrupt differentiation toward a trophoblast giant cell phenotype and instead promote development of the invasive trophoblast cell lineage (Cowden Dahl, Fryer, et al, 2005; Cowden Dahl, Robertson, et al, 2005; Gultice et al, ; Chakraborty et al, , ). These responses are dependent upon HIF signaling, which redirects the epigenetic landscape and gene expression of trophoblast cells (Chakraborty et al, , ). Hypoxia‐dependent HIF activation drives pivotal events, including the downregulation of E‐cadherin and upregulation of KDM3A, which promotes the expression of MMP12 and a pro‐invasive phenotype (Chakraborty et al, , ).…”
Section: Experimental Manipulation Of Oxygenmentioning
confidence: 99%
“…These responses are dependent upon HIF signaling, which redirects the epigenetic landscape and gene expression of trophoblast cells (Chakraborty et al, , ). Hypoxia‐dependent HIF activation drives pivotal events, including the downregulation of E‐cadherin and upregulation of KDM3A, which promotes the expression of MMP12 and a pro‐invasive phenotype (Chakraborty et al, , ).…”
Section: Experimental Manipulation Of Oxygenmentioning
confidence: 99%